Acid sphingomyelinase promotes diabetic cardiomyopathy via disruption of mitochondrial calcium homeostasis - Yu Wei; Yang Ji; Jiahui Meng; Li Yu; Yongzhong Tang; Wei-Jin Fang (Cardiovascular Diabetology)
Abstract Background Impaired Ca2+ handling is involved in diabetic cardiomyopathy (DCM) progression. The activation of acid sphingomyelinase (ASMase) stimulated cardiomyocytes apoptosis and caused DCM. Here, we aimed to investigate whether ASMase regulates mitochondrial Ca2+ homeostasis by acting on mitochondrial calcium uptake 1 (MICU1) and mitochondria-associated endoplasmic reticulum membranes (MAMs) formation to induce apoptosis during DCM. Methods and results We established a type 2 diabetes model by combining high-fat diet (HFD) with streptozotocin (STZ) injection in wild-type and cardiomyocyte-specific ASMase deletion (ASMaseMyh6KO) mice. ASMase deletion restored HFD/STZ-induced cardiac dysfunction, remodeling, myocardial lipid accumulation and apoptosis. Single cell sequencing and Gene ontology (GO) enrichment analysis pointed to “cardiac muscle contraction” and “positive regulation of mitochondrial calcium ion concentration”, which were confirmed by high glucose (HG, 30 mM) and palmitic acid (PA, 200 μM) induced mitochondrial Ca2+ overload in H9c2 cell lines at time dependence, accompanied by the upregulation of ASMase and MICU1 protein expressions. The similar effects were noted in ASMase overexpressed cardiomyocytes. Interestingly, endoplasmic reticulum (ER) Ca2+ level was decreased at the corresponding time, suggesting that increased mitochondrial Ca2+ level may be derived from ER. Notably, enhanced MAMs formation was found in HG + PA treated H9c2 cells, accompanied by blocked autophagy, similar results were obtained in ASMase overexpressing cells or HFD/STZ hearts. Loss of ASMase prevented HFD/STZ or HG + PA incubation induced cardiac hypertrophy, mitochondrialCa2+ overload, ROS production, autophagy blockage and MICU1 upregulation. Conclusions HFD/STZ-induced ASMase upregulation enhances MAMs formation, promoting mitochondrial Ca2+ overload through MICU1 activation, leading to ROS generation, autophagy blockage and apoptosis in DCM. Therefore, targeting ASMase-MICU1 pathway emerges as a potential therapeutic approach for managing DCM. Graphical Abstract